The analysis of the role of probiotics in preventing and reducing the risk of atherosclerosis - literature review - Monika Łapaj; Małgorzata Cholewa; Agnieszka Gawryś; Joanna Wilk; Julia Czarnota; Katarzyna Cichoń; Magdalena Zapała; Piotr Wójcik; Małgorzata Chyćko; Agnieszka Środoń (Kazimierz Wielki University, 2023)
Atherosclerosis is a chronic inflammatory disease of large and medium-sized arteries underlying cardiovascular disease (CVD), such as myocardial infarction, cerebrovascular stroke and peripheral vascular disease, which is the leading cause of mortality worldwide. It is characterized by deposition of modified lipoproteins, accumulation of immune cells and formation of fibrous tissue in the vessel wall. The disease occurs in vessels throughout the body and affects the function of almost all organs, including the lymphatic system, bone marrow, heart, brain, pancreas, adipose tissue, liver, kidneys and gastrointestinal tract. Many clinical trials of anti-atherosclerotic drugs have not provided satisfactory results, and their use is associated with a significant residual risk of cardiovascular disease and various side effects. Probiotics have recently attracted considerable interest for their potential use to prevent atherosclerosis. This review will discuss the mechanisms of effect and impact of probiotics on atherosclerosis risk factors, as well as the potential use of probiotics in the prevention of atherosclerosis, based on a review of the available literature in the PubMed database from 2019 to 2023 using key words on studies related to this topic.